Using the Elzaki Transform to solve systems of partial differential equations - Athraa N. ALbukhuttar; Yasmin A. AL-Rikabi (Genius Journals, 2022)
In this research, we applied Elzaki transform to obtain the general formulas of solution for a system of partial differential equations with constant coefficients in dimension two. After that, these formulas used for solving some system, whether they are homogeneous or non-homogeneous
Keywords: Elzaki Transform; partial differential equations; differential; coefficients